1997
DOI: 10.1590/s0074-02761997000500023
|View full text |Cite
|
Sign up to set email alerts
|

Role of Immune Complexes from Pacients with Different Clinical Forms of Schistosomiasis in the Modulation of In Vitro Granuloma Reaction

Abstract: Schistosomiasis is a disease whose pathology is strongly related to the granulomatous reaction formed around parasite eggs trapped in host tissues. Studies have shown that the chronic intestinal form (INT) of this infection is associated with a variety of immunoregulatory mechanisms which lead to a diminished granulomatous reaction. Using an in vitro model of granuloma reaction, we show that immune complexes (IC) isolated from sera of INT patients are able to reduce granulomatous reaction developed by peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The fact that the PBMCs from the NI and XTO patients were obtained from two distinct endemic areas may explain the differences between our studies. The population living in endemic areas is heterogeneous, and the immunological profile of each individual is a result of re-infection, delayed hypersensitivity and severity of the disease [5]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the PBMCs from the NI and XTO patients were obtained from two distinct endemic areas may explain the differences between our studies. The population living in endemic areas is heterogeneous, and the immunological profile of each individual is a result of re-infection, delayed hypersensitivity and severity of the disease [5]. …”
Section: Discussionmentioning
confidence: 99%
“…The exudative-necrotic granuloma of the acute phase becomes smaller and contains fewer inflammatory cells. This lack of inflammatory cells appears to be less pathogenic to the liver cells [1-5]. Schistosoma infection causes a range of morbidities, which is influenced to a large extent by the nature of the induced immune response and its effects on granuloma formation.…”
Section: Introductionmentioning
confidence: 99%
“…Immune complexes, usually cleared by reticuloendothelial cells, are probably responsible for some manifestations of the acute phase, such as cerebral and cutaneous vasculitis , Jauréguiberry et al 2007, and pericardial and pleural effusions (Taliberti et al 1978, Lawley et al 1979, Rezende et al 1997.…”
Section: Acute Schistosomiasis Mansonimentioning
confidence: 99%
“…Several factors have been associated to liver fibrosis including the genetic background, the degree of infestation and host immunological response. Initially, experimental studies suggested that type-1 cytokines were associated with granuloma formation (Leptak & McKerrow 1997, Rezende et al 1997. However, more recent date point to the importance of type-2 cytokines such as IL-4 and IL-13 in inducing fibrosis and the ability of IL-12 and IFN-γ to decrease it (Wynn et al 1994, Chiaramonte et al 1999b, Jankovic et al 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Liver fibrosis is the most important pathological finding in schistosomiasis, being registered in about 5% of chronically S. mansoni infected patients (Bina & Prata 2003). Although initial experimental studies suggested that type-1 cytokines were associated with granulomatous reaction to S. mansoni infection (Leptak & McKerrow 1997, Rezende et al 1997, its clear from current data that type-2 cytokines play a primary role in inducing fibrosis, whereas the IFN-γ (type-1 cytokine) acts as an endogenous down regulator of the response (Wynn et al 1994, Chiaramonte et al 1999a, Jankovic et al 1999. Simultaneous infection between HTLV-I and Strongyloides stercoralis decreases the predominant type-2 immune response in patients with strongyloidiasis (Neva et al 1998, Porto et al 2001a) as well as S. stercoralis-specific and total IgE antibodies (Neva et al 1998, Porto et al 2001b).…”
mentioning
confidence: 99%